1999
DOI: 10.1007/s004180050351
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical properties of nerve fibres supplying accessory male genital glands in the pig. A colocalisation study

Abstract: Immunohistochemical studies have been performed to investigate the occurrence and coexistence of two catecholamine-synthesising enzymes, tyrosine hydroxylase and dopamine-beta-hydroxylase, and several neuropeptides, including neuropeptide Y, vasoactive intestinal polypeptide, Leu5-enkephalin, somatostatin, calcitonin gene-related peptide and substance P, in nerve fibres supplying porcine accessory genital glands, the seminal vesicles, prostate (body and the disseminated part) and bulbourethral glands. Three ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 55 publications
2
28
1
1
Order By: Relevance
“…In our recent study dealing with the innervation of the porcine AGG we found that many non-adrenergic nerve fibres were localized beneath the tubular epithelium and in the interstitial tissue (Kaleczyc et al, 1999). These fibres coexpressed immunoreactivities to NPY and VIP, VIP and SOM or to NPY and SOM, thus it is likely that these tree peptides coexist within some of the nerve terminals.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our recent study dealing with the innervation of the porcine AGG we found that many non-adrenergic nerve fibres were localized beneath the tubular epithelium and in the interstitial tissue (Kaleczyc et al, 1999). These fibres coexpressed immunoreactivities to NPY and VIP, VIP and SOM or to NPY and SOM, thus it is likely that these tree peptides coexist within some of the nerve terminals.…”
Section: Discussionmentioning
confidence: 87%
“…However, the knowledge of neurochemical properties of cholinergic nerve fibres supplying AGG is still very limited. Therefore, the present study was designed to investigate the presence and coexistence of VAChT and other biologically active substances including NPY, VIP, SOM (neuropeptides found earlier to occur most frequently in nonadrenergic nerve fibres supplying the porcine AGG; Kaleczyc et al, 1999) and DβH in nerve terminals supplying the porcine AGG using single and double-labelling immunofluorescence.…”
mentioning
confidence: 99%
“…The slides were rehydrated in phosphate buffered saline (PBS, pH 7.4) and processed for double-immunofluorescence as described previously (Kaleczyc et al, 1999). Antibodies data are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The relative frequency of nerve fibres (-= not found, ± = single fibres, + = few fibres, ++ = intermediate number of fibres, +++ = many fibres) was assessed using a semi-quantitative method matching that applied in our previous paper (Kaleczyc et al 1999). The evaluation of the structures in the same preparations was independently performed by two investigators.…”
Section: Methodsmentioning
confidence: 99%